2020
DOI: 10.1111/apt.16153
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐glycoprotein 2 (anti‐GP2) IgA and anti‐neutrophil cytoplasmic antibodies to serine proteinase 3 (PR3‐ANCA): antibodies to predict severe disease, poor survival and cholangiocarcinoma in primary sclerosing cholangitis

Abstract: SummaryBackgroundPrimary sclerosing cholangitis (PSC) is associated with progressive liver disease and cholangiocarcinoma. Although risk stratification is crucial for making clinical decisions, it is hindered by a scarcity of proven prognostic markers.AimsTo assess the value of novel anti‐glycoprotein 2 (anti‐GP2) and anti‐neutrophil cytoplasmic antibodies to serine proteinase 3 (PR3‐ANCA) in combination with PSC‐specific clinical and laboratory markers as predictors of quality of life, disease severity, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
1
9
2
2
Order By: Relevance
“…However, one recent study evaluated and subsequently validated ANCA (PR3) in combination with anti-GP2 IgA in PSC patients of European descent. In this study both autoantibodies were found to be associated with worse liver function tests, higher MELD scores, lower transplant free survival, and higher risk of cholangiocarcinoma (Wunsch et al, 2021). Whether this will translate to regular use within the clinical setting and/or international consensus guidelines for PSC management remains to be seen.…”
Section: Antineutrophil Cytoplasmic Antibodiesmentioning
confidence: 68%
“…However, one recent study evaluated and subsequently validated ANCA (PR3) in combination with anti-GP2 IgA in PSC patients of European descent. In this study both autoantibodies were found to be associated with worse liver function tests, higher MELD scores, lower transplant free survival, and higher risk of cholangiocarcinoma (Wunsch et al, 2021). Whether this will translate to regular use within the clinical setting and/or international consensus guidelines for PSC management remains to be seen.…”
Section: Antineutrophil Cytoplasmic Antibodiesmentioning
confidence: 68%
“…45 ANCA positivity may be associated with worse cholestasis and more severe biliary stricturing 46,47 , and it has been suggested as a marker for PSC-IBD subphenotypes 48 as well as increased risk for CCA. 49 IgA antibodies against glycoprotein 2 have been observed in approximately 50% of people with PSC independent of the presence of IBD; these antibodies may identify a subgroup of patients at increased risk of CCA 49,50 and decreased transplantfree survival. 49 Thus, anti-glycoprotein 2 and PR3-ANCA might have prognostic relevance but demonstration of additional value in comparison with known prognostic markers is required.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Auch wenn die PSC häufig positive Autoantikörper (p-ANCA in bis zu 93%, ANA in 8 – 77% und Anti-SMA in 0 – 83% der Patient*innen) aufweist, so haben diese im Gegensatz zur Diagnostik der autoimmunen Hepatitis (AIH) und der primär biliären Cholangitis hier eine geringe Relevanz 32 , 33 . Eine besondere Rolle könnte in Zukunft dem Anti-Glycoprotein-2-Antikörper (Anti-GP2 IgA) und dem antineutrophilen zytoplasmatischen Antikörper gegen Proteinase 3 (PR3-ANCA) zukommen, welche als prognostische Antikörper Hinweise auf einen schwereren Krankheitsverlauf sowie ein erhöhtes Risiko für hepatobiliäre Tumoren liefern können 34 .…”
Section: Primär Sklerosierende Cholangitis (Psc)unclassified
“…Die transiente Elastografie zeigt eine im Verlauf der folgenden 12 Monate mit 7,5 kPa gebesserte Lebersteifigkeit.FALLBEISPIEL Fall 2Der 33-jährige Herr L. stellt sich mit seit einem Monat bestehenden rezidivierenden leicht-bis mittelgradigen Oberbauchschmerzen sowie einem ausgeprägten nächtlichen Juckreiz vor. In der klinischen Untersuchung zeigt sich eine leichte Druckdolenz im kunft dem Anti-Glycoprotein-2-Antikörper (Anti-GP2 IgA) und dem antineutrophilen zytoplasmatischen Antikörper gegen Proteinase 3 (PR3-ANCA) zukommen, welche als prognostische Antikörper Hinweise auf einen schwereren Krankheitsverlauf sowie ein erhöhtes Risiko für hepatobiliäre Tumoren liefern können[34].…”
unclassified